Geoinspired syntheses of materials and nanomaterials. (23rd May 2022) - Portehault, David; Gómez-Recio, Isabel; Baron, Marzena A.; Musumeci, Valentina; Aymonier, Cyril; Rouchon, Virgile; Le Godec, Yann
Abstract : State-of-the-art synthesis pathways towards novel inorganic materials and nanomaterials are presented in the light of their relationship with geosciences, showing how geological phenomena can inspire innovative synthesis methods and materials. Abstract : The search for new materials is intimately linked to the development of synthesis methods. In the current urge for the sustainable synthesis of materials, taking inspiration from Nature's ways to process matter appears as a virtuous approach. In this review, we address the concept of geoinspiration for the design of new materials and the exploration of new synthesis pathways. In geoinspiration, materials scientists take inspiration from the key features of various geological systems and processes occurring in nature, to trigger the formation of artificial materials and nanomaterials. We discuss several case studies of materials and nanomaterials to highlight the basic geoinspiration concepts underlying some synthesis methods: syntheses in water and supercritical water, thermal shock syntheses, molten salt synthesis and high pressure synthesis. We show that the materials emerging from geoinspiration exhibit properties differing from materials obtained by other pathways, thus demonstrating that the field opens up avenues to new families of materials and nanomaterials. This review focuses on synthesis methodologies, by drawing connections between geosciences and materials chemistry, nanosciences, green chemistry, and environmental sciences.